Harmful societies : understanding social harm - Pemberton, Simon (Simon Adrian) (Bristol : The Policy Press, 2015)
This book is the first to theorise and define the social harm concept beyond criminology and seeks to address these omissions. In doing so, it provides a platform for future debates, in this series and beyond.
Title from publisher's bibliographic system (viewed on 11 Mar 2022).
Keywords: Criminology -- Philosophy; State crimes; Justice